A teleportation protocol in Schwarzschild-de Sitter space - Sergio E. Aguilar-Gutierrez; Ricardo Espíndola; Edward K. Morvan-Benhaim (Journal of High Energy Physics)
Abstract We propose a new information transfer protocol for de Sitter space, using black holes as energy reservoirs. We consider antipodal observers in pure de Sitter space in the Bunch-Davis state. They can store Hawking modes from the cosmological horizon in a box. Alternatively, due to thermal fluctuations in de Sitter space, black holes formed through a pair-creation process can be used as energy reservoirs. We focus on the Nariai black hole case, which corresponds to an equilibrium state. Once the black hole is produced, energy pulses can be released into its interior, opening a traversable wormhole. We provide bounds for the amount of information that can be transferred. Specializing in (1+1)-dimensions, we explore how the teleportation protocol leads to an explicit geometric description of the information transmitted through an island region. The protocol uncovers quantum information aspects of de Sitter space, independently of any particular realization of de Sitter space holography.